2016
DOI: 10.1007/s00508-016-1069-7
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of cytomegalovirus infections in Croatia

Abstract: Objectives: Cytomegalovirus (CMV) is endemic worldwide, with marked differences in the seroprevalence rates between countries. The aim of this study was to analyze the seroprevalence of CMV infection in Croatia. Methods:During a three year period (2013)(2014)(2015), 2438 consecutive serum samples collected from Croatian residents were tested for the presence of CMV IgM and IgG antibodies using enzyme-linked immunoassay. IgM/IgG positive samples were further tested for IgG avidity. Results:The overall seropreva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…The seroprevalence in our area was comparable with the prevalence found in the Eastern Mediterranean countries, where the seroprevalence average was 92% (12). In Croatia, in the years 2005-2009, the women of reproductive age had a CMV seroprevalence of 75.3% while between the period 2013-2015 this indicator reached 78% (17,18). These studies showed an increase in seroprevalence over the years contrary to the results obtained in our study.…”
Section: Discussionsupporting
confidence: 60%
“…The seroprevalence in our area was comparable with the prevalence found in the Eastern Mediterranean countries, where the seroprevalence average was 92% (12). In Croatia, in the years 2005-2009, the women of reproductive age had a CMV seroprevalence of 75.3% while between the period 2013-2015 this indicator reached 78% (17,18). These studies showed an increase in seroprevalence over the years contrary to the results obtained in our study.…”
Section: Discussionsupporting
confidence: 60%
“…CMV recurrence was found in 0–15% of hemodialysis patients, with a median value of 7% [ 49 – 51 ], and the CMV seroprevalence reached 92.3% [ 50 ].…”
Section: Who Is the Patient At Risk Of CMV Recurrencementioning
confidence: 99%
“…Depending on the country and its state of development, 25–90% of the worldwide population is CMV seropositive (2, 3) with prevalence higher in older adults (4). Once infected with CMV, the immune system is unable to eliminate the virus, resulting in persistent latent infection.…”
Section: Introductionmentioning
confidence: 99%